Gracz-turysta. Przewodniki po grach i kształtowanie doświadczenia użytkownika - Chojnacki, Marcin M. (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article addresses the issue of the gamer-tourist. The author discusses it from the perspective of a specific reception attitude, consisting in transferring behaviours and expectations typical of virtual tourism to gameplay. The article also takes a closer look at the issue of guides targeted at gamers, specific paratexts that can shape the user experience by formatting the vision of gameplay.